Juventude, gênero fanfiction e letramento digital: um estudo das práticas de leitura e escrita no ensino médio - Anderson Nunes Rocha (2019)
This research intended to investigate the genre of fanfiction, identifying possible contributions to the digital literacy and the reading and writing proficiency in High School. In this perspective, an attempt was made to answer the following research problem: How does the school exploit the social literacy of its students, especially those resulting from its social practices, for the development of reading and writing skills? In order to answer this question, it was necessary to know the space-time of school learning and to deepen in the studies that contemplate the digital literacy and fanfiction. Also known as fanfic, an abbreviation of the term fan fiction, it is a discursive genre whose production is characterized by fictional narratives. It is a genre constructed from texts written by third parties, non-profitable, and its authors use fictional characters or universes, either from literature, cinema, comics or any other media. For the accomplishment of this study, the methodology of the research involved bibliographical survey, documentary and field research, through a case study. As for the context of the research, a public high school was selected from the State of Minas Gerais, located in the metropolitan region of Belo Horizonte, and the participants of the research were a Portuguese Language teacher and a class of high school first year students. Data collection was done through the application of an online questionnaire, participant observation in the classroom and in the computer lab, as well as the application of interviews with students who participated in reading and writing practices with the genre fanfiction, organized and applied all the time of the research. The choice was the theoretical references which contemplate the contributions of authors who research Youth and High School: Sposito (2000), Garbin (2009), Sales (2014); the scope of digital technology: Lévy (1999), Prensky (2001), Martinez (2006); about fanfiction: Vargas (2005), Buzato (2007), Snyder (2010), Teixeira and Gomes (2015), Campos (2016); and on the proficiency of reading and writing in High School: Schneuwly and Dolz (2013), Rojo (2013), Alves (2015), Gomes (2016, 2017), among others who collaborated for the study in question. The results of the investigation revealed that the practices of fanfiction represent an important alternative for the development of reading and writing of students, also bringing contributions to digital literacy. It becomes, therefore, a practice which can be adopted in the school scope for the development of reading, writing and digital literacy of the students.